Effects of hand hygiene education and individual feedback on hand hygiene behaviour, MRSA acquisition rate and MRSA colonization pressure among intensive care unit nurses. Issue 6 (30th October 2014) - Chun, Hee‐Kyung; Kim, Kyung‐Mi; Park, Ho‐Ran
Abstract : This study was conducted to increase the frequency and level of thoroughness of hand hygiene practice by nurses, and to assess the influence of the methicillin‐resistant Staphylococcus aureus (MRSA) acquired incidence rate and the MRSA colonization pressure in a medical intensive care unit (MICU). A total of 24 MICU nurses received hand hygiene education and individual feedback of hand hygiene frequency and method after a session of education, and two posteducation evaluations were followed. The frequency of hand hygiene ( P = 0.001) and the methodology score of hand hygiene increased significantly ( P = 0.001). The MRSA acquisition rate decreased significantly, from 11.1% before the education to 0% after ( P = 0.014). The MRSA colonization pressure decreased significantly from 39.5% to 8.6% after the education sessions ( P = 0.001). This indicates that providing individual feedback after hand hygiene education was very effective in increasing nurses' hand hygiene frequency and improving hand hygiene method; furthermore, it was expected to decrease health care‐associated infections.